Efecto comparativo de la interacción de inmunomoduladores en la productividad de pollos de carne línea cobb avian 48. - Ascate Ramos, Eyder Javier (2015)
This work was carried in the farm Tizal SAC, located in Chao, province of Virú, Department of La Libertad; in the months of August to October 2014. To determine the comparative effect of the interaction of immunomodulators on productivity line broiler chickens Cobb Avian 48. 400 chickens were evaluated for separate in control treatment and immunomodulatory treatment. Immunomodulatory treatment had a mean total final weight of 2,50 kg, while the control treatment had an average of 2,43 kg. Statistically significant differences (p>0,05) between the averages of the two treatments were not calculated. Parameter for weight gain, treatment with immunomodulatory achieved a total average of 2,7 kg, while the control treatment obtained 2,2 kg. Highly significant statistical difference (p<0,01) among treatments for feed conversion characteristic is determined, treatment with immunomodulatory had an overall average with a value of 1,7 and the control treatment was 1,8; determined statistically significant differences (p<0,05). On the consumption of food, immunomodulator therapy had an overall average of 4,3 kg and the control treatment was 4,2 kg. Statistically significant differences (p>0,05) were not calculated. Treatment with immunomodulatory a percentage mortality 6% while the control treatment had 5% was calculated. Statistically significant differences (p>0,05) were not calculated.